Consulta de enfermagem na escola: perfil de saúde com enfoque na saúde auditiva do adolescente - Lopes, Flavia Conceição (2013)
Introduction: The school is a space privileged for actions of health turned to the adolescents, because it collects great part of the young persons of the community being a space of socialization, formation and information. The consultation of nursing in the school environment can be a strategy, for captivation of young persons, for evaluation of his health with sights to the planning of actions of promotion of the individual and collective health, being inserted in the proposals of the National Program of School Health. Objective: To develop and to value the consultation of nursing at the school environment, like strategy for clinical evaluation, psychosocial and of the hearing adolescents health. Method: Intervention study, exploratory, quantitative and descriptive. They were carried out consultation of nursing with 63 adolescents in a public school of the local authority of Curitiba. There was prepared a protocol of evaluation of the health with the definition of diagnoses of nursing, the analysis of the profile one proceeded psychosocial and clinically, with approach in the hearing health of the school adolescents. Resulted: The profile of the adolescents who participated of the consultation of nursing was a 68 % of the feminine sex, the age average was of 16,5 years, and familiar income of 4 minimum wages. Among the aspects of the development psychosocial, the analysis of the school performance, it pointed to high rate of disapproval (62 %) and problems of apprenticeship in one or more disciplines (78 %). The clinical aspects, what more stood out were: 39,7 % of the adolescents was above the weight (surcharge, obesity degree I and obesity degree II). The arterial high blood pressure (degree 1 or 2) was identified in 27 % of the adolescents. Relative to the hearing habits, the majority was presenting unsuitable habits and risks for hearing loss, being that 57 % was listening to music in high volume with telephone of ear of insertion. The nursing diagnoses (OF) more frequent were: bad-tempered (hearing) perceptive sensory capacity (88,8 %), limited processing of information (77,8 %), made a list to the difficulties of apprenticeship, sedentary way of life (60,3 %) resulted from surcharge (39,7 %) and bad-tempered blood pressure (27 %). The adolescents told to be very satisfied with the Consultation of Nursing and that this satisfaction owed to itself the way with which they were attended by the nurse and because of knowing more on his health, when there is this an indicator of the adaptation of the intervention carried out in the school. Conclusions: The consultation of nursing, carried out in the environment of the school, allowed bigger access to the adolescents and a spacious evaluation of the health of these young persons, identifying problems of health, including those of hearing health that might be prevented with actions of promotion of the individual health and collective. The consultation of nursing allows the precocious identification and treatment of problems of the adolescents, with sights to the development of healthy adults, with life quality.